Evolution of NLR genes in genus Arachis reveals asymmetric expansion of NLRome in wild and domesticated tetraploid species - Muhammad Rizwan; Syed Zeeshan Haider; Abu Bakar; Shamiza Rani; Muhammad Danial; Vikas Sharma; Muhammad Mubin; Ali Serfraz; Muhammad Shahnawaz-ur-Rehman; Sidra Shakoor; Saad Alkahtani; Fozia Saleem; et al. (Scientific Reports, 2023)
Abstract Arachis hypogaea is an allotetraploid crop widely grown in the world. Wild relatives of genus Arachis are the rich source of genetic diversity and high levels of resistance to combat pathogens and climate change. The accurate identification and characterization of plant resistance gene, nucleotide binding site leucine rich repeat receptor (NLRs) substantially contribute to the repertoire of resistances and improve production. In the current study, we have studied the evolution of NLR genes in genus Arachis and performed their comparative genomics among four diploids (A. duranensis, A. ipaensis, A. cardenasii, A. stenosperma) and two tetraploid (wild: A. monticola and domesticated: A. hypogaea) species. In total 521, 354, 284, 794, 654, 290 NLR genes were identified from A. cardenasii, A. stenosperma and A. duranensis, A. hypogaea, A. monticola and A. ipaensis respectively. Phylogenetic analysis and classification of NLRs revealed that they belong to 7 subgroups and specific subgroups have expanded in each genome leading towards divergent evolution. Gene gain and loss, duplication assay reveals that wild and domesticated tetraploids species have shown asymmetric expansion of NLRome in both sub-genome (AA and BB). A-subgenome of A. monticola exhibited significant contraction of NLRome while B-subgenome shows expansion and vice versa in case of A. hypogaea probably due to distinct natural and artificial selection pressure. In addition, diploid species A. cardenasii revealed the largest repertoire of NLR genes due to higher frequency of gene duplication and selection pressure. A. cardenasii and A. monticola can be regarded as putative resistance resources for peanut breeding program for introgression of novel resistance genes. Findings of this study also emphasize the application neo-diploids and polyploids due to higher quantitative expression of NLR genes. To the best of our knowledge, this is the first study that studied the effect of domestication and polyploidy on the evolution of NLR genes in genus Arachis to identify genomic resources for improving resistance of polyploid crop with global importance on economy and food security.